Prawo do informacji publicznej na przykładzie Biuletynu Informacji Publicznej Urzędu Miasta w Białej Podlaskiej: The right to public information on example of the Public Information Bulletin of the City of Biała Podlaska Office - Czapski, Grzegorz (Management and Administration Journal, 2021)
The article is analysing the access to public information according to the legislation order (as of 20 January 2014). The basic definition of the right to public information has been presented in the introduction as well as the list of the subjectsresponsible for making the most information accessible. One of the ways that this responsibility is undertaken is with the aid of the Public Information Bulletin. The Biała Podlaska City Council Public Information Bulletin has been presented as the example if the practical application of it.